Population Pharmacokinetics of Lumefantrine in Pregnant and Nonpregnant Women With Uncomplicated Plasmodium falciparum Malaria in Uganda. (13th November 2013) - Kloprogge, F; Piola, P; Dhorda, M; Muwanga, S; Turyakira, E; Apinan, S; Lindegårdh, N; Nosten, F; Day, NPJ; White, NJ; Guerin, PJ; Tarning, J
Abstract : Pregnancy alters the pharmacokinetic properties of many antimalarial compounds. The objective of this study was to evaluate the pharmacokinetic properties of lumefantrine in pregnant and nonpregnant women with uncomplicated Plasmodium falciparum malaria in Uganda after a standard fixed oral artemether–lumefantrine treatment. Dense venous ( n = 26) and sparse capillary ( n = 90) lumefantrine samples were drawn from pregnant patients. A total of 17 nonpregnant women contributed with dense venous lumefantrine samples. Lumefantrine pharmacokinetics was best described by a flexible absorption model with multiphasic disposition. Pregnancy and body temperature had a significant impact on the pharmacokinetic properties of lumefantrine. Simulations from the final model indicated 27% lower day 7 concentrations in pregnant women compared with nonpregnant women and a decreased median time of 0.92 and 0.42 days above previously defined critical concentration cutoff values (280 and 175 ng/ml, respectively). The standard artemether–lumefantrine dose regimen in P. falciparum malaria may need reevaluation in nonimmune pregnant women. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e83; doi:10.1038/psp.2013.59 ; advance online publication 13 November 2013